Emergency contraception: presently available formulations and controversies surrounding their use. (September 2011) - Bastianelli, Carlo; Farris, Manuela
Emergency contraception, or postcoital contraception, is a modality of preventing pregnancy after unprotected sexual intercourse or to avert potential contraceptive failure. The controversy revolves around the definitions of pregnancy and induced abortion. If one utilizes the medical definition accepted by the WHO, pregnancy only begins with implantation; therefore, there can be no abortion without a pregnancy and emergency contraception can in no way be equated to an abortion. The problem is that – ethically at least – there is a contention that a new human life begins right after the fertilization process is completed through full syngamy. Thus, using these parameters, it becomes vital to ascertain exactly the mechanism of action of postcoital methods. Emergency contraception exists in two different forms: the hormonal and the intrauterine. Hormonal emergency contraception was first proposed by Yuspe in the form of 100 µg ethynyl oestradiol plus 500 µg levonorgestrel taken twice at a 12-h interval. At the end of the 1900s, a second regimen – consisting of 1500 µg of levonorgestrel, within 12 h – was introduced and found in clinical trials to be more effective than the Yuspe regimen, if taken as early as possible after an unprotected intercourse. This method therefore completely replaced the Yuspe regimen in common use. Over the last 20 years, the WHO has developed a third regimen based on the use of the selective progesterone receptor modulator mifepristone; different dosages have been tested: >50, 50–25 and <10 mg, taken as a single dose, and they have been found to be equally effective, although the incidence of a delayed onset of the subsequent cycle increases with higher dosages. Two clinical studies have now compared the levonorgestrel and the mifepristone regimens; the first, conducted by WHO, compared three options: levonorgestrel, given either twice at the dose of 750 µg, or as a single 1.5-mg dose, and mifepristone, at a single dose of 10 mg. The second compared levonorgestrel (750 µg, twice) with mifepristone (10 mg, single dose). Both studies concluded that all regimens possess similar effectiveness. Recently, a new formulation consisting of a new selective progesterone receptor modulator, ulipristal acetate, has been licensed in several European countries and in the USA. At the single dose of 30 mg it shown to be a more potent inhibitor of ovulation than levonogestrel and can be effectively taken until 120 h after unprotected intercourse.